A clinicopathological and molecular analysis of cervical carcinomas with basaloid features. Issue 2 (29th October 2019) - Shi, Haiyan; Shao, Ying; Liu, Qin; Wang, Su; Lu, Weiguo; Lu, Bingjian
Abstract : Aims: To investigate the relationship between adenoid basal carcinoma (ABC), adenoid cystic carcinoma (ACC) and squamous cell carcinoma (SCC) in the uterine cervix. Methods and results: We analysed the clinicopathological and molecular features in two pure ABCs, 15 SCCs with ABC‐/ACC‐like features and seven basaloid SCCs (BSCCs) by chart review, immunohistochemistry, human papillomavirus (HPV) RNA in‐situ hybridisation and fluorescence in‐situ hybridisation. All patients were alive with no evidence of disease, except for one patient with ACC‐like features who died of disease at 18 months post diagnosis. The mixed carcinomas comprised variable SCCs and ABC‐/ACC‐like components displaying vague transitional zones. All components consistently showed diffuse p16, p63 and SOX2, variable cytokeratin (CK)7 and CK17 and rare Ber‐EP4 and MYB expression; there was a substantially lower Ki67 index in pure ABCs and the ABC‐like components. The ACC‐like components showed no myoepithelial differentiation (SMA, calponin and S100) and MYB gene fusions. CK7, CK17 and Ber‐EP4 were characteristically stronger in BSCCs than in the mixed carcinomas ( P < 0.01). High‐risk HPV (HR‐HPV) E6/E7 mRNA was detected in 12 mixed carcinomas and seven BSCCs, but not in pure ABCs. The HR‐HPV mRNA expression was higher in the SCC components and BSCCs than in the ABC‐like components of mixed carcinomas ( P < 0.05). Conclusions: The ACC‐like components in mixed carcinomas probably represent the morphological mimics of salivary ACCs. ABC‐like components may be the potential precursor of the ACC‐like and SCC components. HR‐HPV oncogenes may play a role in the pathogenesis of SCCs with ABC‐/ACC‐like features.